An Industrial systems analysis and design study on Molo's Grill and Resto-Bar - Dunuan, Lara Mia.; Maputol, Arlene; Organo, Maria Cristina; Pe, Jonna (Diliman, Quezon City College of Engineering, 2004)
Molo's Grill is located in Anonas, Quezon City. This Industrial Systems Analysis and Design Study aim to sustain and improve the profit of the restaurant through proper analysis of the entire system. In concluding the study, data was gathered, analyzed, and necessary recommendations were made. Data gathering includes plant visits, interview with key personnel, and documentation. In making the analysis, various tools were used such as the Integrated Plant Audit, Porter?s Model, Seven S Model, SWOT Analysis, and graphs in order to have a grasp of the whole system. The corporate strategy of the system was established by analyzing Molo's mission and vision. In line with this, several business strategies were also discussed. A business strategy is a tactic to fight competition. Also, the functional strategies were presented. Two areas were discussed in relation to this. In the operations area, facilities design and supply management were discussed and the other area is marketing. Discussing in depth the strategies in line with the mission, the following study areas were identified Business strategy, facilities design, Supply Chain Management, and marketing strategy. Three business strategies were composed based on the mission. The first business strategy is to strengthen their hold in the City Hall, Teacher Village, Sikatuna Village, Anonas and V Luna Area. Another strategy is to attract more customers due to the wider variety of dishes in Molo's. These strategies can be accomplished by incorporating a sound marketing strategy. The last proposed business strategy is to improve the ambiance of the restaurant. It was recommended in this part that several fixtures be added to improve overall atmosphere of the place. There are three concerns under Facilities Design. First is the daytime inconvenience experienced by the customers due to extreme heat. To address this, a survey of the different types of insulators was done to compare costs and specifications. Next problem is the underutilized facilities, and improved pricing and advertising strategy was developed for this. Last concern is their problem on housekeeping. General good housekeeping rules were advised to be introduced to the company. Another operations area of study is the supply management. Analysis of the critical attributes that concerns supply management led to the identification of aspects to be developed. These are supplier selection and supplier development. The last major area of study is the marketing strategy. Several marketing strategies were suggested: publicity and advertisements, request write-ups in magazines and newspapers, suggested promotional strategies and provide discounts for the use of the recreational facility. A timeline was used to schedule the necessary implementations of the recommendations.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Molo's Grill; Marketing channels--Management.; Delivery of goods--Management.; Physical distribution of goods--Management.; Customer services--Management.; Industrial procurement; Materials management; System design